ANALISIS PERAN GURU DALAM MENGATASI KENAKALAN SISWA PADA PEMBELAJARAN SOSIOLOGI KELAS X MA MATLA’UL ANWAR - Giska Dewi; Imran Imran; Riama Alhidayah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe title of the study "Analysis of the Role of Teachers in Overcoming the Delinquency of Class X Students in Learning Sociology at MA Matla'ul Anwar Pontianak" Helps Teach Teachers' Role as Guides, Role of Teachers as Guides at MA Matla'ul Anwar Pontianak. The research method used is qualitative. Data collection techniques used were observation, interviews, and documentation studies. The data sources of this study were Sociology teachers and Social Sciences class X MA MA Matla'ul Anwar Pontianak students. The results of this study indicate that the teacher has facilitated overcoming the delinquency of students in class X IPS I. The role of the manager is that the teacher creates a conducive class before learning begins. The teacher also helps students who provide guidance to students who do delinquency. Then, the teacher also acts as a motivator, namely the teacher provides motivation and encourages motivation for students who commit delinquency. Keywords: Teacher Role, Sociology, Learnin Student Delinquency